Oud neg.nr. 71391-71407. 'IJmuiden, vis-aanvoer, -afslag, -transport, -bewerking, -inblikken' - Haas, Joh. de
Oud neg.nr. 71391-71407. 'IJmuiden, vis-aanvoer, -afslag, -transport, -bewerking, -inblikken'.